PERSEDIAAN BARANG DAGANGAN SEBAGAI OBYEK JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT DI PT. BANK INTERNASIONAL INDONESIA Tbk CABANG PADANG - Meryanti, Zurlina ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study of the merchandise stock as fiduciary collateral object in the credit agreement in Padang Brance Office of PT. Bank Internasional Indonesia, Tbk. aimed at investigating the criteria of the merchandise stock as the fiduciary collateral object in Padang Brance Office of PT. Bank International Indonesia Tbk., the effort of Padang Brance Office of PT. Bank Internasional Indonesia, Tbk. to maintain the value of the merchandise stock that it remained to be appropriate with its collateral value in the bank and also how is the process of making the merchandise stock as the object of the fiduciary collateral in Padang Branch Office of PT. Bank Internasional Indonesia, Tbk. The study represented a legal study, which was empirical and juridical in nature. The location of the study was Padang Brance Office of PT. Bank Internasional Indonesia, Tbk., while the complementary information was collected from the resource persons, consisting of 2 (two) employees of Padang Brance Office of PT. Bank Internasional Indonesia, Tbk., 2 (two) public notaries and 2 (two) respondents representing the debtors of Padang Brance Office of PT. Bank Internasional Indonesia, Tbk.. The primary data was collected using an in-field study with questionnaire, while the secondary data was collected using literature study of the books on the existing legislation. Based on the results of the study the criteria of the merchandise stock that was used as the fiduciary collateral in Padang Brance Office of PT. Bank Internasional Indonesia, Tbk. were: they had economic value, the ownership of them might be handed over from the owner to other party, and they had juridical value, which meant that the merchandise might be used to pay off the debt when the debtor failed to keep his or her word. To maintain the value of the merchandise stock to be equal with the value of the bank collateral, the bank or its representative could any time inspect the warehouse where the debtor's merchandise stock was stored and checked them against the list of the regular merchandise stock list. The process of making the merchandise stock as the object of the fiduciary collateral in Padang Brance Office of PT. Bank International Indonesia, Tbk. has been conducted as should be.